The Great Power of Prediction from a Massive Photon Hypothesis - CORNIERE, Henri (JOURNAL OF ADVANCES IN PHYSICS, 2022)
Mass, an inherent property of matter, is calculated directly for the photon particle from the very classical principles of the kinetic theory of gases. That concept of photon mass is nearly as old as physics itself and in fact nothing prevents this approach to be carried out for a so-called quantum particle, not even its minute size. It is not an end result with no perspective nor other outcome. Quite the opposite, a single ponderable tiny photon frees the mind of old ways of thinking and opens up new paths to a broad field of investigation where the very large can then be described and explained by the very small. This reality of a non-zero mass suddenly shows up in the interpretation of many experiments which become clear and simple to comprehend. Besides, that same key particle has the potential to unlock and solve some long lasting major observational issues or enigmas. All this converges upon its acknowledgment and acceptance.